Isolation of stx1 and stx2 genes from clinical and environmental samples of Escherichia coli - Shuvra, Samira Khandaker (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.